A mix method study on the effectiveness of visual topology elements used in entrepreneurship online teaching and learning materials at Universiti Teknologi MARA / Siti Nur Diyana Rahimin , Ghazali Daimin and Hardy Loh Rahim - Rahimin, Siti Nur Diyana; Daimin, Ghazali; Rahim, Hardy Loh (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2022)
Malaysia's Ministry of Higher Education has instructed all public universities to make entrepreneurship a compulsory subject for all students. In online entrepreneurship learning, learning material such as PowerPoint (PPT) acts as the tools used by lecturers to simplify the communication process in transferring the message to students. Communication through visual design is one of the easiest ways to assist students in better understanding, focusing, and engaging more with the content. However, if the learning material is poorly designed, it distracts the students’ learning process, making them more likely to stop. Therefore, to avoid these problems, this study analysed the effectiveness of visual topology elements in entrepreneurship teaching materials in the most prominent university and the pioneer of entrepreneurship education in Malaysia, Universiti Teknologi MARA.